Functional Characterization of MaSPL8 Reveals Its Different Roles in Biotic and Abiotic Stress Responses in Mulberry - Longyan Zheng; Wenhao Zhang; Liuqing Wei; Mengqi Li; Li Liu (Plants)
The Squamosa promoter-binding protein-like (SPL) family proteins plays pivotal roles in plant development and stress adaptation. In this study, we functionally characterized MaSPL8 in mulberry (Morus alba) and investigated its regulatory roles in biotic and abiotic stress responses. MaSPL8 encodes a 364-amino acid protein with a conserved SBP domain and lacks miR156/157 binding sites. Phylogenetic analysis confirmed its orthology to Arabidopsis AtSPL8, albeit with functional divergence. Downregulation of MaSPL8 via virus-induced gene silencing (VIGS) resulted in more susceptibility to Ciboria shiraiana infection, but significantly enhanced resistance to drought and salt stress, as evidenced by reduced oxidative damage, elevated proline accumulation, and increased antioxidant enzyme activities. Transcriptomic profiling of MaSPL8-silenced plants revealed enrichment of differentially expressed genes (DEGs) in brassinosteroid biosynthesis, jasmonic acid metabolism, and oxidative stress responses, suggesting hormone signaling interplay. Furthermore, bioinformatic predictions identified miR5658 and miR4221 as potential post-transcriptional regulators of MaSPL8. This study highlights MaSPL8 as a negative regulator of abiotic stress tolerance and positive regulator of biotic (C. shiraiana) stress tolerance in mulberry and provides insights into its integration with phytohormone pathways. Our findings underscore the evolutionary plasticity of SPL8 genes and propose MaSPL8 as a target for enhancing mulberry’s resilience in challenging environments.